Determinants of Board Composition and Corporate Governance in Chinese Enterprises Since Reforms Began: A Comparison of Controlling Shareholders - Zhang, Cheng; Rasiah, Rajah; Cheong, Kee Cheok (Taylor & Francis, 2018)
This study focuses on the determinants of board size and board independence during an economic transition in China. It contributes to the body of Chinese corporate governance studies by applying the most comprehensive analytical framework to the periods before and after the split-share structure reform. Both static and dynamic estimation methods have been used. Overall, the study found that Chinese board size and independence are jointly determined by the scope of operation, cost and benefit of monitoring, CEO’s influence and other governance factors. Among these factors, the government was the most important player in constituting corporate boards before the split-share structure reform; after the reform, board independence became more important than other governance factors. In addition, when constituting corporate boards, private and market-oriented state enterprises are more concerned about cost than are government-controlled enterprises.